Candle street scene, showing businesses and signs for tin shop and The Riverside Saloon, ca. 1904 - Nowell, Frank H., 1864-1950 (1904)
Caption on image: Street, Candil City, Artic. Photo by F.H. Nowell, 2241. The village of candle is located on the west bank of Kiwalik River, 54 miles northwest of Haycock on the Seward Peninsula. It was established ca. 1901 as a mining camp and named Candle Creek. The Candle post office was established in 1902. In 1950 the population was 105. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number